0477 Comparison of a Non-Contact Sleep Monitoring Device with Wrist Actigraphy in a Sample of Individuals with Chronic Insomnia. (25th May 2022) - Teeter, Naomi; Skeiky, Lillian; Gottlieb, Elie; Raymann, Roy; Buchwald, Dedra; Watson, Nathaniel; Van Dongen, Hans; Hansen, Devon; Finlay, Myles; Peterson, Mary
Abstract: Introduction: Non-contact devices (NCDs) have been developed to measure sleep longitudinally and unobtrusively in the naturalistic home setting. We compared longitudinal measurements from a wrist actigraph (Actiwatch-2, Philips Respironics) and from a NCD (SleepScore Max, SleepScore Labs) in a sample of adults with insomnia Methods: N=71 adults (ages 39.0±13.0y; 50 women) who met ICSD-3 criteria for chronic insomnia and were otherwise healthy participated in an at-home sleep monitoring study. Participants continuously wore the actigraph for one week, then used the NCD to record only nightly sleep periods for the next 8 weeks. Week-by-week within-subject averages and standard deviations (SDs) over days were assessed for five major sleep parameters: total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), time in bed (TIB), and sleep efficiency (SE). These sleep parameters were analyzed with mixed-effects ANOVA comparing week one (actigraphy) to the next 8 weeks (NCD), and correlations between the first week (actigraphy) and second week (NCD) were calculated. Results: Significant differences for actigraphy versus NCD were found for the weekly averages of SOL and WASO (F>25.8, p<0.001). The NCD measured longer average SOL (M±SEM=25.0±1.5min) than actigraphy (12.6±2.0min) and less average WASO (40.5±2.7min) than actigraphy (51.1±3.2min). Further, significant differences were found for the weekly within-subject SDs of TST and WASO (F>7.52, p<0.01). The NCD measured greater SD for TST (71.6±2.8min) than actigraphy (60.0±4.7min) and greater SD for WASO (25.0±1.4min) than actigraphy (19.2±2.2min). Actigraphy and NCD weekly averages were positively correlated for TST, WASO, TIB, and SE (p<0.001), but not SOL (r=0.03, p=0.80). Similarly, weekly within-subject SDs were positively correlated for TST, WASO, TIB, and SE (p≤0.05), but not SOL (r=–0.03, p=0.81). Conclusion: Actigraphy and NCD were not used simultaneously, precluding a direct comparison between these measurement modalities. Nonetheless, in this ecologically valid context, significant differences were only found for the weekly averages of SOL and WASO and for the weekly within-subject variability of SOL and TST, with significant correlations between the devices for all variables except SOL. Although actigraphy tends to underestimate SOL, NCD validation against polysomnography in chronic insomnia is warranted. Support (If Any): NIH grant KL2TR002317; research devices provided by SleepScore Labs.